Impact of kidney dysfunction on hepatic and intestinal drug transporters - Marek Droździk (Biomedicine & Pharmacotherapy, 2021)
Emerging information suggests that pathology of the kidney may not only affect expression and function of membrane transporters in the organ, but also in the gastrointestinal tract and the liver. Transporter dysfunction may cause effects on handling of drug as well as endogenous compounds with subsequent clinical consequences. A literature search was conducted on Ovid and PubMed databases to select relevant in vitro, animal and human studies that have reported expression, protein abundance and function of the gastrointestinal and liver localized ABC transporters and SLC carriers in kidney dysfunction or uremia states. The altered function of drug transporters in the liver and intestines in kidney failure subjects may provide compensatory activity in handling endogenous compounds (e.g. uremic toxins), which is expected to affect drug pharmacokinetics and local drug actions.